Population assessment of the Endangered Nilgiri tahr Nilgiritragus hylocrius in the Anamalai Tiger Reserve, using the double-observer survey method. Issue 1 (18th January 2021) - Suryawanshi, Kulbhushansingh Ramesh; Mudappa, Divya; Khanyari, Munib; Raman, T. R. Shankar; Rathore, Devika; Kumar, M. Ananda; Patel, Jenis
Abstract: The Nilgiri tahr Nilgiritragus hylocrius is an Endangered species of mountain ungulate endemic to the Western Ghats of India, a biodiversity hotspot. Habitat fragmentation, hunting and a restricted range are the major threats to this species. Although several surveys have assessed the species' status, a population estimate based on a scientifically robust method is needed. We used the double-observer method to estimate the population of the Nilgiri tahr in the Anamalai Tiger Reserve, a protected area in the Western Ghats. We walked 257 km of transects across the Reserve, covering 36 grassland blocks (i.e. clusters of montane grasslands that were relatively separate from each other). We counted a minimum of 422 individuals in 28 groups, and estimated the tahr population in the study area to be 510 individuals (95% CI 300–858) in 35 groups. The male:female ratio was 0.71 and the young:female ratio was 0.56. Comparing our estimate with previous surveys suggests that the Nilgiri tahr population in Anamalai Tiger Reserve is stable. We found the double-observer survey method to be appropriate for population estimation and long-term monitoring of this species, and make recommendations for improved field protocols to facilitate the implementation of the method in the tropical mountains of the Western Ghats. Our findings suggest that the Reserve harbours 20–25% of the global population of the Nilgiri tahr, highlighting the area's importance for the conservation of this species.